A Case of ST-Elevated Myocardial Infarction Resulting From Obstructive Intramural Coronary Amyloidosis - Uozumi, Hiroki; Soma, Katsura; Takizawa, Masataka; Shiraishi, Junichi; Aoyagi, Teruhiko; Kobayakawa, Naoshi; Takemura, Tamiko (International Heart Journal, 2010)
A 49-year-old man presenting with ST-elevated myocardial infarction was brought to our emergency department with AL amyloidosis. Baseline coronary angiography showed no significant stenosis of the epicardial coronary arteries, however, coronary artery angiography in response to acetylcholine and coronary flow reserve in response to papaverine were abnormal, which suggested impairment of vascular endothelial function. Myocardial biopsy revealed amyloid deposition exclusively in intramural coronary arteries. Early amyloidosis without myocardial involvement can produce acute coronary syndrome through the combination of spastic epicardial coronary arteries and obstruction of the intramural coronary arteries. In the management of certain patients with acute coronary syndrome, the possibility of cardiac amyliodosis should be taken into consideration.